1953
DOI: 10.1002/path.1700660123
|View full text |Cite
|
Sign up to set email alerts
|

Production of opacity in egg‐yolk broth by staphylococci from various sources

Abstract: GILLESPIE and Alder (1952) described an egg-yolk (E.Y.) reaction of Staphylocoecw aurew (coagulase-positive staphylococcus). About 80 per cent. of strains isolated from human Bources outside hospital produced opacity when grown in egg-yolk broth and were called egg-yolk-positive (E.Y. +) strains. The remaining 20 per cent. were egg-yolk-negative (E.Y. -).The distribution of the reaction among strains isolated from in-patients of this hospital was very different. Most of t'he hospital cultures were E.Y.-.The di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
1

Year Published

1954
1954
1982
1982

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 4 publications
0
13
1
Order By: Relevance
“…Other methods used to type Staph. aureus strains include hemolysin production (Elek & Levy, 1951) lipase production (Alder et al, 1953;Delmotte, 1958), hydrolysis of casein (Lieb & Brenneis, 1961); and pigmentation (Willis et al, 1964). The results of Willis et al on the pigmentation of hospital isolates of Staph.…”
Section: Staphylococcus Aureus Rosenbachmentioning
confidence: 99%
“…Other methods used to type Staph. aureus strains include hemolysin production (Elek & Levy, 1951) lipase production (Alder et al, 1953;Delmotte, 1958), hydrolysis of casein (Lieb & Brenneis, 1961); and pigmentation (Willis et al, 1964). The results of Willis et al on the pigmentation of hospital isolates of Staph.…”
Section: Staphylococcus Aureus Rosenbachmentioning
confidence: 99%
“…THE MICROBIOLOGY of the shell eggs, albumen and whole egg magma has been studied extensively (Haines, 1939;Romanoff and Romanoff, 1949;Brooks and Taylor, 1955;Board, 1964Board, , 1965Board, , 1966Board, , 1968Board, , 1973Vadehra and Nath, 1973). However, no detailed studies of the physicochemical changes produced by growth of microorganisms in egg yolk have been reported except for the egg yolk reaction caused by coagulase-positive staphylococci, Clostridium perfringens and Bacillus species (Gillespie and Alder, 1952;Alder et al, 1953;Macfarlane et al, 1941;Mc-Gaughey and Chu, 1948;Calmer, 1948). Gravani et al (1972) and Gravani (1975) reported that Streptococcus faecalis var liquefaciens produced an "egg yolk separation factor" which caused the separation of homogeneous yolk into two weIl defined layers; the upper layer was clear and oily and the lower layer was thick, viscous and gummy.…”
Section: Introductionmentioning
confidence: 99%
“…Gillespie & Alder (1952) found that about 80 yo of coagulase positive strains of staphylococci isolated from human sources outside hospital were egg yolk positive, whereas all of the 60 coagulase negative staphylococci they examined were egg yolk negative. Alder, Gillespie & Herdan (1953) found that the coagulrtse negative staphylococci of human origin were all egg yolk negative and that most of the coagulase positive staphylococci of human origin were egg yolk positive. Ti1 view of these finchgs i t was decided to investigate tlie possibility of utilizing the egg yolk reaction ill t h r p q~a r a t i o n of a solid selective and differential medium for coagulase positive staphylococci.…”
mentioning
confidence: 95%